Identification and Evolution of the Noncoordination Coupling Relationship between Tourism Poverty Alleviation and Ecological Environments in Poor Mountainous Areas - Qu Qin; Zeli Hu; Anle Liu; Yan Huang; Fengtai Zhang (Discrete Dynamics in Nature and Society)
Tourism poverty alleviation and ecological environments are closely associated with each other’s dissipation structure, which contains various coordinated and noncoordinated coupling states. Based on the perspective of reverse thinking and problem diagnosis, this paper constructs a bridge from uncoordinated pathology to coordinated development. From the perspective of incongruity, the framework model and evaluation index system of tourism poverty alleviation and ecological environments incongruity coupling coordination driving mechanism are constructed. Also, the variation coefficient method is used to calculate the weight of each evaluation index and the coupling relationship and evolution of tourism poverty alleviation and ecological environments in Liupanshui city are analyzed by the noncoordination coupling function. The results suggest the following: (1) During the study period, the poverty alleviation level of tourism in Liupanshui city presents a continuous growth curve. Meanwhile, ecological environment development level depicts rapid growth initially and then slows down and improves further. In this way, it shows different stage characteristics from the tourism poverty alleviation level. (2) The discordant coupling between tourism poverty alleviation and ecological environments in Liupanshui city shows a decreasing curve. So, the noncoordinated development relationship between tourism poverty alleviation and ecological environments is significant.